2018
DOI: 10.1590/abd1806-4841.20187106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological profile of patients with early stage mycosis fungoides

Abstract: BackgroundMycosis fungoides is the most common form of primary cutaneous lymphoma, with an indolent, slowly progressive course and 88% five-year survival rate. The diagnosis is challenging, especially in the early stages, and usually relies on a good clinical-histopathological correlation.ObjectiveThe aim was to establish the clinical and epidemiological profile of patients with early-stage mycosis fungoides.MethodsThis was a retrospective cross-sectional observational study with an exploratory analysis. Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 21 publications
2
41
2
5
Order By: Relevance
“…In line with the literature, the majority (64.8%) of our study group were aged between 50 and 79 years [2,3]. However, in contrast to previous studies the number of females in our MF cohort outnumbered the males (51% vs. 49%) [2,3,[14][15][16]. Concordant with earlier observations, we found that Caucasians were most commonly affected, constituting 56.1% of our patient cohort [2,8,17].…”
Section: Discussionsupporting
confidence: 91%
“…In line with the literature, the majority (64.8%) of our study group were aged between 50 and 79 years [2,3]. However, in contrast to previous studies the number of females in our MF cohort outnumbered the males (51% vs. 49%) [2,3,[14][15][16]. Concordant with earlier observations, we found that Caucasians were most commonly affected, constituting 56.1% of our patient cohort [2,8,17].…”
Section: Discussionsupporting
confidence: 91%
“…Por otro lado, estas lesiones son difíciles de diferenciar de otras anomalías como el eccema, incluso para los propios dermatólogos, lo que aumenta el tiempo transcurrido hasta la derivación. Es frecuente que los pacientes se sometan a más de una biopsia hasta determinar el diagnóstico definitivo, debido a patrones inespecíficos en estadios tempranos de la enfermedad [10][11][12][13][14][15] .…”
Section: Discussionunclassified
“…2 MF typically has an indolent growth phase with an estimated 88% 5-year survival rate. 4 The World Health Organization/ European Organisation for Research and Treatment of Cancer classification for primary cutaneous lymphomas defines multiple subtypes of MF, including classic plaque-stage MF, folliculotropic MF, pagetoid reticulosis, and granulomatous slack skin. The gd subtype is a rare subtype of MF and is characterized by the expression of the gd T-cell receptor (TCRgd).…”
Section: Discussionmentioning
confidence: 99%